Development of Canva Software-Based Interactive Learning Media Using the ADDIE Method - Lise Asnur; Taali; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop interactive learning media for Restaurant Operations 1 course in the D4 Hospitality Management study programme at Padang State University. This course is a compulsory course with a weight of 2 credits, consisting of 1 credit of theory and 1 credit of practice. Currently, this course still uses modules in the form of PDF files that only contain text and images. Therefore, developer software, especially Canva, is needed to create interactive learning media. Canva is an online design tool that can be accessed through websites and apps. This research uses the ADDIE development method, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. However, this study only implemented the first three stages, namely analysis, design, and development. The analysis stage consists of needs analysis and multimedia system analysis. The design stage includes media structure design, content design, and interface design. The result of the development stage is an interactive learning media that is in accordance with the applicable competencies. The initial product was validated by material experts and media experts. Suggestions and input from experts are used for improvement so that the learning media becomes valid and can be used in Restaurant Operations 1 courses.